Imaging the cAMP-dependent signal transduction pathway. (26th October 2005) - Zaccolo, M.; Cesetti, T.; Di Benedetto, G.; Mongillo, M.; Lissandron, V.; Terrin, A.; Zamparo, I.
Abstract : In recent years, the development of new technologies based on the green fluorescent protein and FRET (fluorescence resonance energy transfer) has introduced a new perspective in the study of cAMP signalling. Real-time imaging of fluorescent biosensors is making it possible to visualize cAMP dynamics directly as they happen in intact, living cells, providing important and original insights for our understanding of the spatiotemporal organization of the cAMP/PKA (protein kinase A) signalling pathway.